Analysis of a 3 kg Capacity Coffee Roasting Machine - Yogi Eka Fernandes; Wahyu R; Ali Medi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Coffee is one of Indonesia's most strategic agricultural commodities, contributing significantly to national export revenues and serving as a primary income source for smallholder farmers. However, many small to medium-scale coffee producers still rely on traditional roasting methods that result in inconsistent temperature control, uneven roasting, and suboptimal product quality. This study aims to design, fabricate, and analyze the performance of a 3 kg capacity coffee roasting machine equipped with an LPG-based heating system and an electric motor-driven rotating drum. The machine was designed using Autodesk Inventor Professional 2025 and tested under varying operational conditions, including three roasting temperatures (200°C, 220°C, and 240°C), three roasting durations (10, 15, and 20 minutes), and two drum rotation speeds (40 rpm and 60 rpm). A total of 54 experimental trials were conducted to determine the effect of these variables on moisture content reduction and visual colour characteristics of the roasted coffee beans. Results indicate that the most optimal roasting condition was achieved at at 200°C, 20 minutes, and 40 rpm, yielding an average moisture content reduction of 12.3%, and at 220°C, 15 minutes, and 60 rpm, yielding an average moisture content reduction of 12.1% and producing dark roast beans with uniform colour and appearance. The study demonstrates that higher roasting temperatures combined with longer durations and faster drum rotation speeds significantly enhance moisture evaporation efficiency while maintaining uniform heat distribution. These findings provide practical guidelines for improving coffee processing quality among small-scale producers.